N3 & The Line-Up - Lenzi, M.
For every action there is an equal and opposite reaction. This is Isaac Newton's third law of motion. It sounds simple enough,... and it is. This principle is the one that affects the dive more often than any other principle. This does not mean that other forces and laws are not relevant to diving. I will go into some of them later in this book. For now, let us concern ourselves with Newton's third law of motion and the line-up. To better understand this principle, I will use a simple example; the Voyager space craft. Voyager is traveling through space at a constant speed and direction. There are planetary forces that act on Voyager, however, for our purposes we will assume that none exist to make our point clear. Voyager is traveling in a straight line. How do you get it to veer in a different direction, say towards Pluto? You apply a force and or action. This force is a retrorocket that fires in a direction that applies a force in a specific direction. That force causes a reaction that pushes the spacecraft in the specific opposite direction. That's it! That is all you need to know about this force. If you want to understand it more effectively than buy a physics book. However, this part of the law is all you need to master for now. Although, you do have to know how to apply it correctly.